Role of plaque imaging for identification of vulnerable patients beyond the stage of myocardial ischemia - Kitada, Ryoko; Otsuka, Kenichiro; Fukuda, Daiju (Frontiers in Cardiovascular Medicine, 2023)
Chronic coronary syndrome (CCS) is a progressive disease, and often, acute coronary syndrome (ACS) is the first manifestation. Imaging modalities are clinically useful and help in decision making for the treatment and management of patients with CCS. Accumulating evidence demonstrated that myocardial ischemia is a surogate marker for management of CCS; however, it has limited ability on the prediction of cardiovascular death or non-fatal myocardial infarction. We present a review that highlights recent knowledge of coronary syndromes and discusses the role and limitations of imaging modalites in the diagnosis and management of patients with CAD. The review covers essential aspects of the role of imaging to assess myocardial ischemia, and coronary plaque burden and composition, together with recent clinical trials for lipid-lowering therapy and anti-inflammatory therapy. Additionally, it provides a comprehensive overview of intracoronary and noninvasive cardiovascular imaging modalities and recent understanding of ACS and CCS, with a focus on histopathology and pathophysiology.